Software quality evaluation: a bibliometric analysis and future perspectives - Entringer, Tulio Cremonini; Ferreira, Ailton da Silva (Independent Journal of Management & Production, 2019)
The theme of “Software Quality Evaluation”, and its importance, concerns the standardization of the development processes, in order to guarantee a higher quality of the systems. In this scenario, this theme has gained importance in academic research, due to the emphasis that the theme has increasingly presented to organizations, since they understand that the main objective is to guarantee a final product that satisfies the expectations of the client. In order to verify the scientific scenario in recent years, this work aims to carry out a review of the literature on “Software Quality Evaluation”, based on a bibliometric analysis and review. For this, the method of bibliographic revision with four different phases proposed by Marasco (2008) was used. From the data extracted from the Scopus database, the results of the systematic review and bibliometric analysis were analyzed from the information on publications, citations and approaches of the papers that deal with this subject. As results, the present article showed the academic and practical importance of the studies on “Software Quality Evaluation”. In addition, it is possible to identify gaps in the scientific literature that can be filled by future work in the area, based on the studies developed by specialists.